[Znaczek podziemny z Kornelem Morawieckim, 1987] . Unofficial stamp with Kornel Morawiecki, 1987 - Solidarność Walcząca. (Solidarność Walcząca, 1987)
Red and blue print on golden paper, without perforation. Stamp with "Solidarność Walcząca" imprint, represents Kornel Morawiecki. Price: 50 zł per stamp.